Evaluation of frictional properties and consequences on table ball interaction for different ITTF approved plastic balls - Tiefenbacher, K. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
The purpose of this study is to evaluate influence of table/ball combination on bounce in table tennis. From 2014, a variety of non-celluloid plastic balls have been approved by the ITTF to replace highly flammable celluloid as base material for table tennis balls. Currently, different manufacturers use different type of plastic material and manufacturing process for these new balls. An entire study was performed to compare the interaction between the different types of balls in combination with a selection of table tops. Therefore, hitting experiments have been executed under realistic conditions. Results are used to show the differences in bounce behaviour, but also to check whether the Brody/Durey impact model may be applied for the bounce. This model allows calculation of dynamic parameters Coefficient of Friction (CoF) and Coefficient of Restitution (CoR) from special bounces, which then allows to describe bounce behaviour and thus the consequences on table tennis game. Further to that, there was a check whether it is possible to measure a meaningful CoF from a sliding experiment. At the end, a recommendation was given for a measurement method to classify frictional properties of table/ball combinations in a meaningful way, which could be used for approval purposes.